Engineered PAM-SPION Nanoclusters for Enhanced Cancer Therapy: Integrating Magnetic Targeting with pH-Responsive Drug Release - Dimitra Tzavara; Konstantina Papadia; Argiris Kolokithas-Ntoukas; Sophia G. Antimisiaris; Athanasios Skouras (Molecules)
Background: Nanomedicine approaches for cancer therapy face significant challenges, including a poor tumor accumulation, limited therapeutic efficacy, and systemic toxicity. We hypothesized that controlling the clustering of poly(acrylic acid-co-maleic acid) (PAM)-coated superparamagnetic iron oxide nanoparticles (SPIONs) would enhance their magnetic properties for improved targeting, while enabling a pH-responsive drug release in tumor microenvironments. Methods: PAM-stabilized SPION clusters were synthesized via arrested precipitation, characterized for physicochemical and magnetic properties, and evaluated for doxorubicin loading and pH-dependent release. A dual targeting approach combining antibody conjugation with magnetic guidance was assessed in cellular models, including a novel alternating magnetic field (AMF) pre-treatment protocol. Results: PAM-SPION clusters demonstrated controlled size distributions (60–100 nm), excellent colloidal stability, and enhanced magnetic properties, particularly for larger crystallites (13 nm). The formulations exhibited a pH-responsive drug release (8.5% at pH 7.4 vs. 14.3% at pH 6.5) and a significant enhancement of AMF-triggered release (17.5%). The dual targeting approach achieved an 8-fold increased cellular uptake compared to non-targeted formulations. Most notably, the novel AMF pre-treatment protocol demonstrated an 87% improved therapeutic efficacy compared to conventional post-treatment applications. Conclusions: The integration of targeting antibodies, magnetic guidance, and a pH-responsive PAM coating creates a versatile theranostic platform with significantly enhanced drug delivery capabilities. The unexpected synergistic effect of the AMF pre-treatment represents a promising new approach for improving the therapeutic efficacy of nanoparticle-based cancer treatments.